2016
DOI: 10.1371/journal.pone.0154895
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study Brings to Light the Causes of Screen Failures in Phase 1 Cancer Clinical Trials

Abstract: IntroductionEnrolling cancer patients in phase I clinical trials (P1s) requires that they fulfill specific criteria. Between the time they sign the consent form and the 1st administration of the experimental drug, some patients may be excluded and considered as screen failures (SFs). Our objective was to assess SF patients profiles and the reasons and risk factors for SFs.Materials and MethodsAll patients included in P1s at Gustave Roussy from 2008 to 2013 were reviewed retrospectively. SFs were matched with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…An improved risk assessment could support the clinical decision when enrolling patients in phase I studies as early discontinuation of patients in phase 1 trials most frequently are due to progression and clinical deteoriation. 21 The clinical implementation of the proposed model therefore has the potential to improve selection of patients to phase I trials. Furthermore, low plasma concentration of cfDNA at baseline is correlated with a higher chance of receiving further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An improved risk assessment could support the clinical decision when enrolling patients in phase I studies as early discontinuation of patients in phase 1 trials most frequently are due to progression and clinical deteoriation. 21 The clinical implementation of the proposed model therefore has the potential to improve selection of patients to phase I trials. Furthermore, low plasma concentration of cfDNA at baseline is correlated with a higher chance of receiving further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We could not directly compare survival scores (RMH or GRIm) to our model prediction which is a binary screening status, independent from the time. However, in a cohort similar to ours, RMH score wrongly discarded half of potential good candidates for inclusion in early-phase clinical trials 6 . This is of major concern, because early-phase clinical trials was shown to improve clinical outcomes for up to 30% of patients 27 The screen failure rate observed in this study (including screening and DLT period) may seem high (about 40%), but was consistent with previous reports and can be explained by the known tendency of physicians to be overoptimistic regarding their patients prognosis 7,28 .…”
Section: Discussionmentioning
confidence: 65%
“…The rate of patients not eligible to the trial after this period -defining screening failureusually scales between 10% and 30% [5][6][7] . For patients who actually start the study treatment, there is an additional crucial period -defined as the dose-limiting toxicity (DLT) evaluation period -that usually prolongs of another 28 days the length of time during which if a patient is withdrawn from the trial and not evaluable for DLT (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large patient base—17,000 new cancer patients in 2015—aided referrals for site #6. Screen failures are common and occur due to cancer progression during the screening period and/or poor performance status . The Royal Marsden Hospital prognostic score has been validated by an MD Anderson Cancer Center phase I clinic .…”
Section: Discussionmentioning
confidence: 99%